Effect of Monthly Variations on the Plasma Membrane, Acrosome and DNA Integrities of Spermatozoa in Friesian Holstein Bulls Born in Iraq - Aboud, Qusay; Hatif, Saad (مجلة الانبار للعلوم البيطرية)
This study was aimed to evaluate the influence of months of the year on the quality of semen in Holstein bulls. A study carried out at artificial insemination centre/ Abou-Ghareeb/ western of Baghdad. A total of 160 ejaculates were collected from 15 bulls born in Iraq via the artificial vagina. The age of the bulls ranged between 4 to 5 years and the study period were December to March and September. The semen samples were diluted with Tris base extender. The semen was packed in a straw according to the program of artificial insemination centre. Semen characteristics (plasma membrane, acrosome, and DNA integrities) were evaluated. The results revealed a significant decrease (P≤0.01) in the plasma membrane and acrosome integrity in September as compared with December, January, February, and March. There was a significant decline (P≤0.05) in DNA integrity in September as compared with December, January, February, and March in fresh and frozen semen. In conclusion, the September month had a negative effect on the plasma membrane, acrosome, and DNA percentage in all bulls.